A novel lozenge containing bupivacaine as topical alleviation of oral mucositis pain in patients with head and neck cancer: a pilot study. (September 2016) - Mogensen, Stine; Treldal, Charlotte; Sveinsdottir, Kolbrún; Jensen, Kenneth; Kristensen, Claus A.; Mogensen, Torben S.; Petersen, Janne; Andersen, Ove
Abstract : Abstract: Introduction: Oral mucositis induces severe oral pain in head and neck cancer patients. There is at this point no effective pain treatment without considerable side effects. Objective: The aim of this pilot study was to investigate pain reduction in oral cavity and pharynx in patients with head and neck cancer (HNC) with oral mucositis, the location of anesthetic effect, and duration of pain relief, after a single-dose administration of a 25 mg bupivacaine lozenge. Methods: Ten patients with HNC suffering from oral mucositis pain were included. The patients assessed pain in the oral cavity and pharynx on a visual analogue scale (from 0 to 100 mm) at baseline and up to 3 hours after the lozenge was dissolved. Possible adverse events were registered. Results: The baseline pain was 51 mm (range: 30–73 mm) in the oral cavity and 58 mm (range: 35–70 mm) in the pharynx. When the lozenge was dissolved, both oral (−27 mm; range: −3 to −52 mm; P = 0.0003) and pharynx pain (−20 mm; range: −3 to −45 mm; P = 0.008) were significantly reduced. After 180 minutes, the mean reduction in pain was significant in the oral cavity (−18 mm; range: −8 to −30 mm; P < 0.0001) but not in the pharynx (−8 mm; range: +4 to −23 mm; P = 0.12). No adverse events were observed. Conclusion: The results indicate that the bupivacaine lozenge has a clinically significant and long-lasting pain-relieving effect on pain because of oral mucositis in patients with HNC. Abstract : A bupivacaine lozenge has a clinically significant and long-lasting pain-relieving effect in patients with head and neck cancer with pain due to oral mucositis.